STUDY ON THE ASSOCIATION OF OBESITY INDICES WITH INFLAMMATORY MARKERS IN PRE-DIABETES AND DIABETES - PRADEEP KUMAR; SHAILAZA SHRESTHA; MAHENDRA PRASAD; PREETI SHARMA; MOHIT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In this study, the main objective was to evaluate the association of markers of obesity with the inflammatory markers in pre-diabetes and diabetes. Methods: This study recruited 300 participants (100 control group, 100 pre-diabetic group, and 100 diabetic group). The anthropometric variables such as body mass index (BMI), waist-hip ratio (WHR), and waist circumference (WC), and biochemical variables such as fasting blood glucose, glycated hemoglobin, uric acid, C-reactive protein (CRP), fibrinogen, interleukin-6 (IL-6), and adiponectin were analyzed in each participant by standard methods. Results: The present study documented significantly high values of BMI and WHR in patient (pre-diabetic and diabetic) groups compared to the control group. Similarly, the level of adiponectin decreased and that of uric acid, CRP, fibrinogen, and IL-6 increased significantly. Both BMI and WC were correlated significantly with inflammatory mediators in diabetic patients. The correlation with adiponectin was negative. In the pre-diabetic group, a significant correlation was observed only between WHR, adiponectin, and uric acid. Conclusion: This study supports the fact that obesity-induced systemic inflammation of low grade is significantly associated with pre-diabetes and diabetes, thereby keeping these individuals at high risk of future complications especially cardiovascular diseases.